Milk market of small scale artisan cheese factories in selected livestock watersheds of Honduras and Nicaragua - Holmann, Federico J. (2001)
Surveys were made of rural artisan cheese factories located in the region of Olancho, Catacamas, and Juticalpa in Honduras (n=10) and in Esquipulas and Muy-Muy in Nicaragua (n=13). The objective was to analyze the milk market of small rural artisan cheese factories in livestock watersheds of Honduras and Nicaragua to determine if: